#TITLE_ALTERNATIVE# - PRATIWI (NIM 10105083), NOVITA
Water flow in an inclined open channel often causes roll wave phenomenon. This phenomenon looks as if the surface slides down or falls. Here we study the flow in an inclined channel using the Saint Venant equation. This equation consists of continuity equation and momentum equation. By observing the uniform condition with monochromatic wave disturbance, we will find a relation between the slope and bottom friction that causes roll wave. Analytical study using the linearized Saint Venant Equation shows that if the angle of the channel is larger than four times bottom friction, the monochromatic wave will be unstable and roll wave will appear. In terms of current, instability will occur if the current is larger than two times the speed linear wave. Numerically we apply the flux vector splitting method to the linearized Saint Venant equation. Numerical simulation using a set of parameters that satisfies stability gives the evolution of a monochromatic wave running to the right as a stable wave. For a simulation using a set of parameters that leads to instability, roll wave phenomenon does not appear yet.